Critical theory diverse objects, diverse subjects - Lehmann, Jennifer M., 1956- (Current perspectives in social theory ;, 2003)
The contributions in this 22nd volume of "Current Perspectives in Social Theory" explore the arguments for and against a view of the world in which multiple, distinct and conflicting societies differ both over time and contemporaneously.